Spiropyrans Containing the Reactive Substituents in the 2H-Chromene Moiety - B. S. Lukyanov; Yu. S. Alekseenko; E. L. Mukhanov; M. B. Lukyanova; A. V. Metelitsa; K. N. Khalanskij; V. V. Tkachev; O. N. Ryashin (International Journal of Photoenergy)
Some spiropyrans containing functional substituents in the [2H]-chromene part of the molecule were synthesized and their photochromic properties in solution and solid state were investigated. The presence of the formyl group in the [2H]-chromene fragment enhances the possibility to show photochromic properties in solution.